Information Demand and Supply of Rural Elderly: Based on a Field Investigation of Village C, Taiyuan City, Shanxi Province - Kun HUANG, Qionghao GUO, Chenyu ZHOU, Lei LI (Nongye tushu qingbao xuebao)
[Purpose/Significance] The aging of the Chinese population is an issue that is becoming increasingly salient. The considerable migration populations from urban to rural areas has exacerbated the aging process in rural regions of China. In recent years, the Chinese government demonstrated a commitment to addressing the urban-rural disparity, with a particular focus on enhancing the living standards of the elderly people in rural areas. However, given the substantial elderly population base, there may also be disparities in the information needs of the elderly across regions with varying degrees of economic development. The objective of this study is to provide insights into the information demand and supply of elderly people in rural areas, promote elderly care information services in rural areas, and enhance the quality of life and well-being of elderly people in rural areas, thereby promoting rural revitalization. [Methods/Processes] This study conducted survey and interview, investigating the motivations for information seeking, the information sources utilized, the information needs and satisfaction, as well as difficulties encountered in the process of obtaining information. Based on Maslow's hierarchy of needs theory, we investigated the information demands of elderly people from five aspects: physiological, safety, emotional, esteem, and self-realization. This study conducted a field survey in C Village, Taiyuan City, Shanxi Province, and collected valid questionnaires from 109 elderly people. At the same time, two village committee staff members were interviewed, and online information such as government websites was also collected. [Results/Conclusions] The findings indicate that rural elderly people primarily obtain information for entertainment and adaptation to the social environment. Rural elderly mainly acquire information through the utilization of personal networks, namely family members, television broadcasts, neighbors, and friends. Nonetheless, the elevated demand and high satisfaction represent physiological information needs, while the high demand and low satisfaction category focuses on safety and emotional information needs. Elderly people are easily constrained by their physical health status and information literacy when seeking information. At the same time, the insufficient level of regional economic development and investment in public cultural facilities serve as impediments to rural elderly people's access to information. Besides, from the perspective of information supply, the roles and collaborative mechanisms of government departments, village committees, social organizations, and families as the primary providers must be reinforced. A model of information demand and supply service for rural elderly people is finally constructed from the perspective of multiple subjects. It demonstrates that government departments play an important role in ensuring and providing support for elderly care services in terms of policies, funding, and management. The village committee fulfills a coordinating, monitoring, and service role, while enterprises and social organizations serve as supplementary forces for elderly services in rural areas. Families are an important support for promoting the upward mobility of elderly information needs. and relevant countermeasures are proposed. In conclusion, this study proposes recommendations concerning the role of multiple subjects in addressing information needs characterized by high demand but low satisfaction. Suggestions have been put forward to improve economic and health levels in response to low demand and low satisfaction of information needs. Efforts should be made to strengthen the multi-agent collaborative mechanism, improve the information acquisition ability and quality of life of rural elderly people, and narrow the gap between urban and rural elderly care services.